Crucial Mutations of Spike Protein on SARS-CoV-2 Evolved to Variant Strains Escaping Neutralization of Convalescent Plasmas and RBD-Specific Monoclonal Antibodies - Ding, Chengchao; He, Jun; Zhang, Xiangyu; Jiang, Chengcheng; Sun, Yong; Zhang, Yuqing; Chen, Qingqing; He, Hongliang; Li, Wenting; Xie, Jiajia; Liu, Zhirong; Gao, Yong (Frontiers in Immunology, 2021)
Small number of SARS-CoV-2 epidemic lineages did not efficiently exhibit neutralization profile, while single amino acid mutation in the spike protein has not been confirmed in altering viral antigenicity resulting in immune escape. To identify crucial mutations in spike protein that escape humoral immune response, we evaluated cross-neutralization of convalescent plasmas and RBD-specific monoclonal antibodies (mAbs) against various spike protein-based pseudoviruses. Three of 24 SARS-CoV-2 pseudoviruses containing different mutations in spike protein, including D614G, A475V and E484Q, consistently showed altered sensitivity to neutralization by convalescent plasmas. A475V and E484Q mutants are highly resistant to neutralization by mAb B38 and 2-4, suggesting that some crucial mutations in spike protein might evolve SARS-CoV-2 variants capable of escaping humoral immune response.